Effect of muscular strength, asymmetries and fatigue on kicking performance in soccer players - Maly, T.; Sugimoto, D.; Izovska, J.; Zahalka, F.; Mala, L. (International Journal of Sports Medicine, 2018)
The aim of this study was to determine the effect of muscular strength, strength asymmetries, and fatigue on the speed and accuracy of an instep kick in soccer players. We measured ball velocity (BV) and kicking accuracy (KA) in the preferred (PL) and non-preferred leg (NPL) before (PRE) and after (POST) physical load in the PL. Maximum peak muscle torque of the knee extensors and flexors in the PL and NPL as well as ipsilateral knee flexors and knee extensors ratio (H:Q ratio) for both legs were assessed. BV was significantly decreased in POST physical load (5.82%, BVPRE=30.79±1.70 m·s-1, BVPOST=29.00±1.70 m·s-1, t19=3.67, p=0.00, d=1.05). Instep kick accuracy after the physical load worsened by an average of 10% in the most accurate trials. Results revealed a significant decrease in instep kick accuracy after physical loading (KAPRE=2.74±0.70 m, KAPOST=3.85±1.24 m, t19=-3.31, p=0.00, d=1.10). We found an insignificant correlation between H:Q ratio and KA in PRE test value, whereas a lower ipsilateral ratio (higher degree of strength asymmetry) in the POST physical load significantly correlated with KA in all angular velocities (r=-0.63 up to -0.67, p=0.00).